The detail as a temporal device of the architectural restoration in Portugal, in the 19th century: the case of the train in the convent of Madre de Deus, in Lisbon (Palíndromo, 2022)
In Lisbon, in the 19th century, during the restoration of the Madre de Deus Convent, a building founded in the 16th century, a steam train entering a tunnel was carved on the chapitel of one of the columns of one of the cloisters. We intend to demonstrate that this was not a mistake, but the figuration of an explicitly modern detail that functioned as a temporal device that distinguished the changes introduced by the restoration from the original parts of the building, in line with the philological restoration by Camillo Boito, even when they recreated the original architectural style, in accordance with the principles of the stylistic restoration by Eugène-Emmanuel Viollet-le-Duc. In a restoration still dominated by the doctrine of Viollet-le-Duc, represents a first impact of the reception of Boito's ideas in Portugal.
Keywords: 19th Century Architecture; Restoration; Madre Deus Convent; Chapiter; Train